Europe without defence: The states of Europe have to re-evaluate the interrelationship between political sovereignty, military effectiveness and economic efficiency - Christian Mölling (Stiftung Wissenschaft und Politik (SWP), 2011)
NATO's operation in Libya has revealed significant deficiencies in European defence. It is not only that Europe's defence capability is chronically underdeveloped and the USA's support is dwindling. The resources that would allow European states to deal with these deficits are likewise shrinking dramatically. The defence budget crunch has strategic consequences. Unlike the »usual« underfinancing of European defence establishments in the last decade, budget constraints are now changing the aims and means of defence policy abruptly, substantially and in a long-term perspective. If Europe does not halt the rapid depletion of its defence resources, both the structure of its armed forces and its defence industry base will be turned upside down. At the end of this process, we will be left with a Europe that is incapable of defending its strategic interests outside its borders
Keywords: 320